Does Social Trust Stimulate Regional Eco-Efficiency? Evidence From China - Yan, Youliang; Cheng, Jixin; Wang, Yunmin; Li, Yating (Frontiers in Environmental Science, 2021)
Ecological efficiency is an important part of economic sustainable development. As the transitional economy with “weak institution” features, the informal institutions have a vital role in China’s economic development. Using panel data from 2001 to 2016, this paper estimates eco-efficiency of China’s 30 provinces based on Super-SBM DEA with global Malmquist index and investigates the governance role of a typical informal institution, namely social trust, in regional eco-efficiency. Empirical results show the following: (1) From 2001 to 2016, the accumulated changes of regional eco-efficiency are all greater than 1, indicating that all provinces in China are actively changing its development mode to improve eco-efficiency. (2) Social trust plays a significantly positive role in improving regional eco-efficiency. (3) Moreover, this effect is more pronounced in regions with poor legal development. (4) The mechanism tests further show that social trust can improve regional eco-efficiency through promoting regional green innovation and developing regional finance. Our findings shed light on the implications of informal institutions, and in particular on the value of social trust in realizing green economic development in emerging market.